Mercury records from natural archives reveal ecosystem responses to changing atmospheric deposition. - Chen Q; Wu Q; Cui Y; Wang S (Oxford University Press, 2024)
Global ecosystems face mercury contamination, yet long-term data are scarce, hindering understanding of ecosystem responses to atmospheric Hg input changes. To bridge the data gap and assess ecosystem responses, we compiled and compared a mercury accumulation database from peat, lake, ice and marine deposits worldwide with atmospheric mercury deposition modelled by GEOS-Chem, focusing on trends, magnitudes, spatial-temporal distributions and impact factors. The mercury fluxes in all four deposits showed a 5- to 9-fold increase over 1700-2012, with lake and peat mercury fluxes that generally mirrored atmospheric deposition trends. Significant decreases in lake and peat mercury fluxes post-1950 in Europe evidenced effective environmental policies, whereas rises in East Asia, Africa and Oceania highlighted coal-use impacts, inter alia. Conversely, mercury fluxes in marine and high-altitude ecosystems did not align well with atmospheric deposition, emphasizing natural influences over anthropogenic impacts. Our study underscores the importance of these key regions and ecosystems for future mercury management.
Keywords: GEOS-Chem; ecosystem recovery; mercury pollution; natural archive; policy evaluation